Association between phase angle, anthropometric measurements, and lipid profile in HCV-infected patients (Clinics, 2013)
OBJECTIVE: The objective of this study was to investigate the associations between phase angle, anthropometric measurements, and lipid profile in patients chronically infected with the hepatitis C virus. METHODS: A total of 160 consecutive patients chronically infected with the hepatitis C virus and who received treatment at the hepatitis C outpatient unit of our hospital from April 2010 to May 2011 were prospectively evaluated. Bioelectrical impedance analysis, anthropometric measurements, and serum lipid profile analysis were performed. RESULTS: Twenty-five patients were excluded. A total of 135 patients with a mean age of 49.8¡11.4 years were studied. Among these patients, 60% were male. The phase angle and BMI means were 6.5¡0.8°and 26.5¡4.8 kg/ m2, respectively. Regarding anthropometric variables, mid-arm circumference, mid-arm muscle circumference, and arm muscle area had a positive correlation with phase angle. In contrast, when analyzing the lipid profile, only HDL was inversely correlated with phase angle. However, in multiple regression models adjusted for age and gender, only mid-arm circumference (p = 0.005), mid-arm muscle circumference (p = 0.003), and arm muscle circumference (p = 0.001) were associated with phase angle in hepatitis C virus-infected patients.CONCLUSIONS: In conclusion, phase angle is positively correlated with anthropometric measures in our study. However, there is no association between phase angle and lipid profile in these patients. Our results suggest that phase angle is related to lean body mass in patients chronically infected with hepatitis C virus.